2018
DOI: 10.1080/02656736.2018.1539776
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency ablation of liver cancers adjacent to the gallbladder without gallbladder isolation under contrast-enhanced ultrasound monitoring: a preliminary study

Abstract: Purpose: The purpose of this study was to investigate the feasibility, safety and efficacy of intra-procedural contrast-enhanced ultrasound (CEUS) monitoring of the radiofrequency ablation (RFA) of liver cancers adjacent to gallbladder (GB) without GB isolation. Materials and methods: From May 2016 to July 2017, patients with liver cancers adjacent to GB (10 mm) who intended to undergo ultrasound-guided RFA without GB isolation in our hospital were prospectively enrolled. During the RFA procedures, CEUS was em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Thermal ablation includes laser ablation (LA), radiofrequency ablation (RFA), high-intensity focused ultrasound (HIFU) and microwave ablation (MWA), among which RFA is the most common [ 15 ]. RFA has been routinely used for the treatment of liver, vascular and other diseases [ 16 ]. In addition, RFA is also effective in the treatment of benign thyroid nodules, but it has been reported that it is less effective in the treatment of solid nodules [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thermal ablation includes laser ablation (LA), radiofrequency ablation (RFA), high-intensity focused ultrasound (HIFU) and microwave ablation (MWA), among which RFA is the most common [ 15 ]. RFA has been routinely used for the treatment of liver, vascular and other diseases [ 16 ]. In addition, RFA is also effective in the treatment of benign thyroid nodules, but it has been reported that it is less effective in the treatment of solid nodules [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…To date, thermal ablation for FNH has only been reported in adults (14). Our team has also reported (15) the application of ultrasound-guided ablation for lesions near the gallbladder, thus avoiding the need for cholecystectomy. Accordingly, we chose to perform ultrasound-guided percutaneous MWA for this patient.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, in the present study, we retrospectively reviewed whether the combination of RFA and previous TAE (1-2 days before) could minimize LTP and increase OS rates. It is a challenge to perform RFA for HCC in these highrisk locations, including the hepatic dome, subcapsular area, gastrointestinal tract, or gallbladder, among others [23][24][25][26], because the ablation volume must be limited to avoid damage to surrounding organs. Therefore, we applied a 3DVAPS to assist with RFA for HCC to achieve multiple ablation spheres of a fixed size covering the target and to observe the spatial location relationship between the tumor and surrounding vital organs more intuitively.…”
Section: Discussionmentioning
confidence: 99%